Association between perceived social support and sociodemographic characteristics in diabetic and/or hypertensive elderly (Research, Society and Development, 2022)
Objective: to characterize the sociodemographic profile of elderly people with diabetes and/or hypertension and to verify the association between sociodemographic characteristics and perceived social support. Methodology: Cross-sectional study, involving 371 elderly people, aged 60 years and over, diagnosed with Diabetes Mellitus and/or Arterial Hypertension and monitored in basic health units in Campina Grande-PB. The analyzed variables were selected from the sociodemographic questionnaire and Social Support Inventory. Multiple linear regression analysis was performed to verify how sociodemographic variables impacted levels of perceived social support. Results: There are significant associations between perceived social support and marital status (c2(3) = 10.954, p